Green ICT & Energy : From Smart to Wise Strategies. - Appelman, Jaco H. (Sustainable energy developments ;, 2014)
"This book provides the connection between the growing body of literature on sustainability and the topics of energy and ICT. It aims to show how stakeholders active in this area need to play their part ensuring that the ICT-sector evolves towards a sector that can lead through "greening by IT" and also shows that it can "green its own IT" as well. This is the first book that integrates two seemingly incompatible approaches to sustainability: efficiency and effectiveness. The book builds on the efficiency initiatives already taken by industry, but it is not a "how-to-do-it manual". It offers insight in state of the art approaches to green IT and greening by IT. Attention to important stakeholders outside the sector, e.g. policy makers and the field of education, makes this book comprehensive. A more encompassing view on ICT and sustainability is offered to the reader and, as such, managers in higher education, educators, CIO's, policymakers and regulators are inspired to integrate their efforts and to contribute to a transition of one of the most important and prominent sectors in our global economy."--Publisher's description